التدابير الوقائية والاحترازية للحدث في قانون الأحداث القطري والفقه الإسلامي: دراسة تحليلية = Preventive and precautionary measures for 'the child' between the Qatari child law and the Islamic jurisprudence: an analytical study - Aldosari, Mohammed Benayan; Arif, Arif Ali; Zakariyah, Habeebullah (Al Hikmah Research & Publication Centre, 2023)
This paper examines the preventive measures adopted in the Qatari child law and Islamic jurisprudence, at the time international interest in juveniles (children) is high, which was reflected in international agreements, which majorly includes (the Convention on the Rights of the Child) in 1989 AD. The researcher used the analytical and comparative approach, following the preventive measures in the Qatari child law, as well as in Islamic jurisprudence references, offered views and analyzed them, and compared the Qatari child law with the opinions of the Islamic jurists. The study comes to find and establish the capacity and comprehensiveness of Islamic law in dealing with the child and protecting him from delinquencies through preventive measures before and after his birth, such as choosing a good mother for him before his birth, and choosing a good name, good education and other preventive measures after his birth. The Qatari child Law is concerned with the child before delinquency and put in place corrective and preventive measures for him. However, there are gaps in the measures adopted by the Qatari law to protect the child contrary to Islamic Sharia, which is evident in the scantiness of these measures and their need for review. ------------------------------------------------------------ يتناول هذا المقال التدابير الوقائية المتبعة في قانون الأحداث القطري، والفقه الإسلامي، تزامناً مع الاهتمام الدولي للأحداث )الأطفال( الذي انعكس في الاتفاقات الدولية والتي من أهمها )اتفاقية حقوق الطفل( عام 1989 م. وقد استخدم الباحث فيه المنهج التحليلي والمقار ن، بتتبع التدابير الوقائية في قانون الأحداث القطري، وكذا في كتب الفقه الإسلامي، وعرض الأقوال وتحليلها، ومقارنة قانون الأحداث القطري بأقوال الفقهاء. وقد توصلت الدراسة إلى جملة من النتائج من أبرزها: سعة الشريعة الإسلامية، وشموليتها في التعامل مع الحدث وحمايته من الانحراف عن طريق تدابير وقائية قبل ولادته وبعدها، وقبل ولادته كاختيار الشريك المناسب، وبعد ولادته كاختيار الاسم الحسن، وحسن التربية وغير ذلك من التدابير الوقائية. واهتمام قانون الأحداث القطري بالحدث قبل الانحراف ووضع تدابير وقائية إصلاحيه له، إلا أن هناك قصور في التدابير التي نص عليها القانون لحماية الأحداث خلافًا للشريعة الإسلامية وهو ما يظهر في قلة تلك التدابير وحاجتها إلى المراجعة